Dietary implications in acetylsalicylic acid intolerance: Statement by the Food Allergy Working Group of the German Society for Allergology and Clinical Immunology (DGAKI) - Dölle-Bierke, Sabine; Plank-Habibi, Sibylle; Schäfer, Christiane; Ahrens, Birgit; Ballmer-Weber, Barbara; Beyer, Kirsten; Blümchen, Katharina; Huttegger, Isidor; Jappe, Uta; Kleine-Tebbe, Jörg; Lange, Lars; Lau, Susanne; et al. (Allergo Journal, 2020)
Background: Acetylsalicylic acid (ASA) may cause difficult-to-treat symptoms of the airways, skin, or gastrointestinal tract in hypersensitive patients. Due to the chemical relationship between salicylic acid and ASA, a role of a low-salicylate diet has been discussed. Methods: This review evaluates whether low salicylate diets are meaningful from an allergological or nutritional–physiological perspective. Results: The body’s arachidonic acid metabolism plays a crucial role in the pathogenesis of ASA intolerance. Despite their chemical affinity, ASA and salicylic acid affect the arachidonic pathway differently. The intake of salicylic acid with food is low compared to therapeutic doses of ASA. There is increasing evidence that protective effects of a high fruit and vegetables diet is related in part to the intake of salicylates. In salicylate-low diets, fruit and vegetables are reduced, harboring the risk of an insufficient diet and malnutrition. Conclusion: Dietary therapy in ASA-intolerant patients is not recommended.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Anti-inflammatory diet; ASA; Aspirin; COX; Salicylic acid